Education, Governance, and Trade- and Distance-Related Technology Diffusion: Accounting for the Latin America-East Asia TFP Gap, and the TFP Impact of South America's Greater Distance to the North - Maurice Schiff; Yanling Wang (Institute of Labor Economics (IZA), 2017)
This paper examines the impact of education, governance and North-South trade- and distance-related technology diffusion on TFP in the South, focusing on South America (SA), Mexico, Latin America (LA) and East Asia for the 32-year period preceding the Great Recession (1976–2007) in a new model that integrates models of trade-related and distance-related international technology diffusion. Our model's explanatory power is 38% (62%) greater than that of the main trade-related (distance-related) model. Findings are: i) TFP increases with education, trade, governance (ETG) and imports' R&D content, and declines with distance to the North; ii) an increase in LA's ETG to East Asia's level raises LA's TFP by some 100% and accounts for about 75% of its TFP gap with East Asia; iii) raising LA's education to East Asia's level has a larger impact on TFP and on the TFP gap than raising governance or openness; iv) the TFP impact on South America relative to Mexico due to its greater distance to US-Canada (Europe) (Japan) is -18.9 (-2.13) (-9.78)%, with an overall impact of -12.4%.
Keywords: F13; I25; O19; O47; 330; education; governance; trade; distance; technology diffusion; productivity impact; Latin America; East Asia